Middle-aged and older people with urgent, unaware, and unmet mental health care needs: Practitioners' viewpoints from outside the formal mental health care system - Akinori Takase; Yuki Matoba; Tsutomu Taga; Kae Ito; Tsuyoshi Okamura (BMC, 2022)
Abstract Background Mental health challenges are highly significant among older individuals. However, the non-utilization of mental health services increases with age. Although universal health coverage (UHC) was reported to reduce unmet health care needs, it might not be sufficient to reduce unmet mental health care needs from a clinical perspective. Despite the existence of UHC in Japan, this study aimed to explore the factors related to the non-utilization of formal mental health care systems among middle-aged and older people with urgent, unaware, and unmet mental health care needs. Methods Purposeful sampling was used as the sampling method in this study by combining snowball sampling and a specific criterion. The interviewees were nine practitioners from four sectors outside the mental health care system, including long-term care, the public and private sector, as well as general hospitals in one area of Tokyo, where we had conducted community-based participatory research for five years. The interviews were conducted by an interdisciplinary team, which comprised a psychiatrist, a public health nurse from a non-profit organization, and a Buddhist priest as well as a social researcher to cover the broader unmet health care needs, such as physical, psychosocial, and spiritual needs. The basic characteristics of the interviewees were enquired, followed by whether the interviewees had case of middle-aged or older individuals with urgent, unaware, and unmet mental health care needs. If the answer was yes, we asked the interviewees to describe the details. The interviews pertinent to this study were conducted between October 2021 and November 2021. In this study, we adopted a qualitative descriptive approach. First, we created a summary of each case. Next, we explored the factors related to the non-utilization of formal mental health care systems by conducting a thematic analysis to identify the themes in the data collected. Results The over-arching category involving "the factors related to an individual person" included two categories, as follows: 1) "Individual intrinsic factors," which comprised two sub-categories, including "difficulty in seeking help" and "delusional disorders," and 2) "family factors," which comprised "discord between family members," "denial of service engagement," "multiple cases in one family," and "families' difficulty in seeking help." The over-arching category "the factors related to the systems" included four categories, as follows: 1) "Physical health system-related factors," which comprised "the indifference of physical healthcare providers regarding mental health" and "the discontinuation of physical health conditions," 2) "mental health system-related factors," which comprised "irresponsive mental health care systems" and "uncomfortable experiences in previous visits to clinics," and 3) "social service system-related factors," which comprised "the lack of time to provide care," "social service not allowed without diagnosis," and "no appropriate service in the community," as well as 4) " the lack of integration between the systems." Apart from the aforementioned factors, "the community people-related factor" and "factors related to inter-regional movements" also emerged in this study. Conclusions The results of this study suggest a specific intervention target, and they provide further directions for research and policy implementation. The suggested solutions to the issues pertinent to this study are as follows: the recognition of the ways in which older people may inadequately understand their health or be unaware of available services, the building of a therapeutic alliance for "the individual intrinsic factors." Regarding the "family factors," the solutions include the provision of particularly intensive care for families with family discords, families with multiple cases, and families who find it difficult to seek help, as well as making intensive efforts for ensuring early involvement after contact with health care services. Regarding the "the factors related to the systems," the solutions include the implementation of mental health education campaigns aimed at enhancing mental health knowledge among non-mental health professionals, as well as formulating and implementing reforms ensuring that such professionals are increasingly responsible especially with regard to emergency inpatient care. It also include listening without ageism in clinical practice, the expansion of social services regarding human resources and the flexibility of use which increases the breadth of the types of care, as well as facilitating the integration between the associated health care systems. Further suggestions include encouraging community residents to join social security systems as well as the provision of particularly intensive care for people who have just moved in.